NILAI KEADILAN DALAM EKONOMI SYARIAH - Syaakir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2019)
Justice has a variety of meanings covering all aspects of human life, especially in the economic field. Justice occupies a central position in the Islamic economic system. With various meanings of fairness, in broad outline is a condition where all levels of society get equal treatment, equality of compensation, the right to life, and enjoy development without anyone feeling disadvantaged. Justice demand that resources be distributed equitably to all people through Islamic economic instruments. The concept of economic justice in Islam emphasizes equality of rights and avoids social imbalances caused by economic inequality. By creating economic justice for society it will present the concept of brotherhood. With a great commitment to brotherhood and justice, all resources which are sacred mandates are used to realize sharia maqashid.